1984
DOI: 10.1021/jm00376a011
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and .beta.-adrenergic blocking activity of new aliphatic and alicyclic oxime ethers

Abstract: We describe the synthesis and pharmacological properties of two new series of aliphatic and alicyclic beta-adrenergic blockers, most of them containing a cyclopropyl ring. They belong either to 2-hydroxy-3-(tert-butylamino)propyl ether A or 2-hydroxy-3-tert-(butylamino)propyl ketoxime ether B derivatives. The O-[2-hydroxy-3-(tert-butylamino)propyl] dicyclopropyl ketoxime 5 exhibited a beta-adrenergic antagonist activity comparable to that of propranolol. It was found that ketoxime ethers B generally showed hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1985
1985
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…Where these data were available in the literature, the experimental logP values (Craig 1990) were similar to the predicted ones, except in the case of verapamil (3Á79 vs 5Á52 predicted). Also, the experimental logD values (Bouzoubaa et al 1984;Zamora et al 1988;Betageri & Dipali 1993) were in agreement with the predicted ones, except in the case of quinine. The predicted value for this compound (logD À0Á06) was obviously inaccurate compared with the experimental value (logD 2Á1 at pH 7Á4) determined by Zamora et al (1988).…”
Section: Drug Permeation Properties (Pd50 and H)supporting
confidence: 80%
“…Where these data were available in the literature, the experimental logP values (Craig 1990) were similar to the predicted ones, except in the case of verapamil (3Á79 vs 5Á52 predicted). Also, the experimental logD values (Bouzoubaa et al 1984;Zamora et al 1988;Betageri & Dipali 1993) were in agreement with the predicted ones, except in the case of quinine. The predicted value for this compound (logD À0Á06) was obviously inaccurate compared with the experimental value (logD 2Á1 at pH 7Á4) determined by Zamora et al (1988).…”
Section: Drug Permeation Properties (Pd50 and H)supporting
confidence: 80%
“…An oxypropanolamine side chain linked to an aromatic ring are the chemical features required for β-blocking activity. However, the alteration of these features as the intercalation of an imino group in the side chain does not abolish the interaction on β-adrenoceptors but can lead, in some cases, to potent β-antagonists [28,29]. To evaluate the effect caused by a different type of insertion of pharmacophore oxypropanolamine chain in the 1,4-BT moiety that possesses short-lived blood pressure reducing effects in experimental animals [30], 6-, 7-, 8-oxypropanolamine and 6-, 7-, 8-acetimidoyloxypropanolamine of 3,4-dihydro-3-oxo-2H-1,4-benzothiazine were prepared [31].…”
Section: Spr-210mentioning
confidence: 99%
“…Based on the chemical structure of the classical aryloxypropanolamine β-adrenoceptor blockers, Imbs et al [2] showed that the insertion of an oxime ether in place of the typical ether linkage retained β 2 -antagonist activity; e.g., IPS 339 (Figure 1). Other oxime ethers were also synthesized and reported to have β 2 -blocking activity with high potency, e.g., falintolol (Figure 1) [3,4]. Although the above mentioned cardiovascular effects are mainly attributed to β 1 -blockage, β 2 -adrenoceptor antagonists might be potentially interesting as experimental tools [5], or for testing in pulmonary arterial hypertension [6].…”
Section: Introductionmentioning
confidence: 99%